Conservative Management of Pneumoperitoneum in Necrotising Enterocolitis- Is it Possible? - Pandey, Anand; Singh, Shailendra P; Gupta, Vipin; Verma, Rajesh (Journal of Neonatal Surgery, 2016)
Introduction: Necrotizing enterocolitis (NEC) is a common in neonatal intensive care unit (NICU) patients; especially in premature and low birth weight ones. Surgery is indicated when there is pneumoperitoneum. Other therapies include conservative observation or primary peritoneal drain (PPD). This study was conceived to evaluate peritoneal tapping, rather than primary peritoneal drain (PPD) as a treatment of NEC. Material and Methods- This prospective observational study conducted from December 2012 to December 2014 and including all patients of NEC having pneumoperitoneum on X-ray. Results- There were 12 patients of NEC. Seven patients responded to single peritoneal tapping. Three patients needed one more tapping. Laparotomy was required in remaining two patients. One patient, who underwent laparotomy, expired due to severe sepsis. The mean duration of follow up was 4.83 months (range 2 to 8). Conclusion- Peritoneal tapping in NEC who develops pneumoperitoneum appears to be a viable option. Further studies in this regard may substantiate this mode of therapy.